Nancy Richardson for School Board Headquarters on N. Wishon Avenue - Watkins, Howard K. (1975)
Nancy Richardson Ray Walker (glasses), Carol Walker (red coat) Peter Oswald (green coat), foreground: Mario Olmos and Mary Louise Frampton